(untitled) (Editora Impacto Científico, 2025)
Introduction: The field of Physical Education has expanded considerably, encompassing areas beyond the traditional gyms and schools. With a diverse range of activities, the professional works in sports preparation, health promotion and assists all age groups, including people with special needs. In this context, the role of the Physical Education Professional (PEF) in hospital environments emerges as a relevant and little-explored topic, promoting rehabilitation and contributing to health promotion. Aim: The aim of this study was to investigate the potential for PEFs to work in hospital environments, evaluating their participation in multidisciplinary teams, their activities and their importance for patients’ rehabilitation and health promotion. Methodology: The research was carried out by means of a bibliographical review and analysis of previous work related to the work of the PEF in hospital environments. Information was gathered on the activities carried out by PEFs, their integration into healthcare teams and the benefits of their work for patients. Results: The results indicate that the potential of the PEF to work in hospital environments is recognized and considered indispensable. The professional performs a variety of activities, including the rehabilitation of patients with heart disease, stroke victims, cancer patients, pregnant women and the elderly, among others. Despite this, their presence in multidisciplinary teams is still limited, mainly due to budgetary issues. However, their inclusion is essential to complement the work of other health professionals and promote the well-being of patients.